Chronic Cluster Headache with an Atypical Presentation and Treatment Response. (29th December 2016) - Santos, Telma; Morais, Hugo
Abstract : The management of cluster headache (CH) may be challenging. We report a 50-year-old male with recurrent attacks of dull and severe unilateral periorbital pain, lasting 30–45 minutes, twice a day, exclusively during sleep, and accompanied by ipsilateral rhinorrhea and lacrimation. The pain switched sides within every attack. CH treatment was initiated but the patient maintained recurrence rates compatible with chronic CH, even after increasing verapamil to 460 mg/day. Afterwards we decided to add lithium (800 mg/day). With this treatment the severity and recurrence of CH substantially decreased, despite the patient's autonomous decision to take lithium only during the acute phase of the cluster. The exclusively alternating location and the excellent response to short cycles of lithium represent two unique features of CH.